miR-193a-3p Mediates Placenta Accreta Spectrum Development by Targeting EFNB2 via Epithelial-Mesenchymal Transition Pathway Under Decidua Defect Conditions - Li, Na; Hou, Rui; Yang, Tian; Liu, Caixia; Wei, Jun (Frontiers in Molecular Biosciences, 2021)
Objective: To clarify the role of microRNA-193a-3p (miR-193a-3p) in the pathogenesis of placenta accreta spectrum. Methods: The placental tissue expression levels of miR-193a-3p and Ephrin-B2 (EFNB2) were compared between a placenta accreta spectrum group and a control group. Transwell migration and invasion assays were used to verify the effect of miR-193a-3p and EFNB2 on HTR-8/SVneo cells cultured in human endometrial stromal cell (hESC)-conditioned medium. Epithelial-mesenchymal transition (EMT)-related proteins were examined by western blotting to establish whether the EMT pathway was altered in placenta accreta spectrum. To determine whether EFNB2 is a target gene of miR-193a-3p, luciferase activity assays were performed. Results: miR-193a-3p was upregulated but EFNB2 downregulated in the placenta accreta spectrum group and EFNB2 was a direct target of miR-193a-3p. Overexpression or inhibition of miR-193a-3p revealed that miR-193a-3p promoted the migration and invasion of HTR-8/SVneo cells cultured in hESC-conditioned medium. Furthermore, EMT was induced, as shown by increased N-cadherin, vimentin, MMP2, and MMP9 and decreased E-cadherin in the placenta accreta spectrum group and in HTR-8/SVneo cells transfected with miR-193a-3p mimics or si-EFNB2. The negative effect of miR-193a-3p inhibitor was reversed by co-transfection with si-EFNB2 in function studies and in analyses of EMT-related proteins in vitro. Conclusion: miR-193a-3p which upregulated in placenta accreta spectrum group increases HTR-8/SVneo cell migration and invasion by targeting EFNB2 via the EMT pathway under decidua defect conditions to lead to placenta accreta spectrum.